Accounting for crack closure effects in out-of-phase TMF crack growth with extended hold times. (May 2022) - Loureiro-Homs, Jordi; Almroth, Per; Palmert, Frans; Gustafsson, David; Simonsson, Kjell; Eriksson, Robert; Leidermark, Daniel
Highlights: Crack closure explains crack growth behaviour for CM 247 LC. Crack closure explains crack growth under prolonged hold times. Simulations can replicate plasticity-induced crack closure. The proposed analytical model estimates crack opening levels. Abstract: The crack growth behaviour of the alloy CM 247 LC is investigated for out-of-phase TMF and isothermal tests at the same temperature as the minimum temperature in the TMF tests. The results suggest that it is possible to characterise crack growth behaviour if experimental corrections for crack closure are accounted for. The replication of these experimental tests using a numerical FE-solver results in similar crack growth behaviour, suggesting that the main mechanism in place is plasticity-induced crack closure. A pragmatic analytical model to characterise crack closure including hold time effects is proposed. The comparison of the response from this model with the experimental and numerical results suggests that the proposed analytical model is capable to approximate crack closure effects for cases where substantial creep deformation is to be expected.